Revising the distribution of mangrove forests in South Africa and changes in growth of mangrove species along a latitudinal gradient - Bolosha, Uviwe (Rhodes University, Faculty of Science, Botany Department, 2017)
Mangrove forests are a diverse assemblage of trees and shrubs that are adapted to a saline and tidally inundated environment. The global spread of mangrove species is affected by climate, with most confined to areas that are warmer and moist. At a global scale, temperature limits the distribution of mangrove forests but on a regional scale and local scale, rainfall, river flow and tidal exchange have a strong effect on the distribution and biomass of mangrove forests. Other factors that play a role in limiting growth and distribution of mangroves include accessibility of suitable habitats for growth and also conditions that are suitable for propagule dispersal. The objectives of this study were to review the distribution of mangroves in South Africa and determine the number of extreme temperature events that may limit further distribution and secondly to measure growth rates of mangrove species at Mngazana and Nahoon Estuary and the nutrient pools in the sediment of these forests. In 1982, Ward and Steinke published a list of estuaries where mangroves were present. The current study sampled the population structure, microclimate and level of expansion in two estuaries within and outside of the published range. The minimum, maximum temperature and number of extreme temperature events were measured using iButtons. Mangrove expansion will be limited by minimum temperatures (1.1 ° C) and an increase in extreme temperature events (830) (<5 ° C and 5- 10 ° C) at the latitudinal limits. Expansion of A. marina at Kwelera and Tyolomnqa Estuary was evident but sapling survival was low. Mangroves have expanded within and outside the range proposed by Ward and Steinke (1982), but are limited by physical factors, restricted by the presence of saltmarsh and other estuarine macrophytes and natural disturbance regimes. An increase in population growth was recorded over the years at both Mngazana and Nahoon Estuary. Nutrients, (ammonium, nitrates + nitrites and soluble reactive phosphorus) varied amongst sites and were related to seasonality. Nitrogen in both estuaries was available in the form of ammonium (NH4) and its concentration was generally higher (1.3-76.2 pm) than other forms of nitrogen (0.07-6.3 µm). Soluble reactive phosphorus (SRP) was higher during the wet seasons in both estuaries. An increase in porewater salinity since 2007 (41.3 practical salinity unit (PSU)) was measured at Mngazana and this is a result of freshwater abstraction and low rainfall. A. marina saplings and adults grew significantly faster at Nahoon Estuary (the distributional limit) (11.1 ± 1.1 cm year-¹) compared to Mngazana Estuary (5.3 ± 1.8 cm year-¹). Different mangrove species and forests respond differently to environmental factors and changes in mangrove distribution is expected in South Africa but changes are expected to happen slowly and opportunistically.
Keywords: Mangrove ecology -- South Africa; Mangrove forests -- South Africa; Mangrove plants -- South Africa -- Effect of temperature on